IMPLEMENTATION OF PUBLIC INFRASTRUCTURE AND FACILITIES HANDLING PROGRAM IN EAST CILANDAK VILLAGE, PASAR PEKAN DISTRICT, SOUTH JAKARTA ADMINISTRATIVE CITY - Adee Fatahilah; Murtir Jeddawi; Rizari Rizari (Jurnal Scientia, 2023)
Jakarta has a relatively low number of settlements and the level of comfort index for residents of Jakarta is still at an average level. This is due to the need for better public infrastructure. The Provincial Government of DKI Jakarta has made a program for Handling Infrastructure and Public Facilities (PPSU) to accelerate the functioning of locations/infrastructures and assets of public facilities and damaged, dirty or unsuitable utilization. The Program was launched to optimize services to the community. This research aims to explain how the implementation of Public Infrastructure and Management Handling Program (PPSU) in North Cilandak sub-district, explains the factors that influence the implementation and analyze strategies in improving the program. This study uses a descriptive qualitative research method with an inductive approach. Data collection comes from observations, interviews and documentation. Data analysis techniques in this study use data reduction, data presentation and conclusion drawing and finding strategies by SWOT analysis. Based on the result found by the author, the implementation of PPSU in North Cilandak sub-district needs to berunning optimally. As has noyet to beeen to be maximum are the support of community participation to engage in environmental cleaning up activities, the frequent accumulation of rubbish heaps, dirty sewers and illegal graffiti have not been handled. The program’s success has not been achieved because of the low performance of PPSU officers in terms of work motivation and less discipline. The author recommends a strategy by periodically evaluating the performance of PPSU officers and improving the operational (monitoring, coaching and supervising) operations of PPSU officers intensively and sustainably.